Nitrogen and Phosphorus Application Effects on Pearl Millet Forage Yield and Nutritive Value - D. D. Serba; A. Obour (Kansas Agricultural Experiment Station Research Reports, 2017)
There is limited information on the nitrogen (N) and phosphorus (P) fertilizer requirement of pearl millet forage in dryland systems. Determination of optimum N and P rates for pearl millet forage production in dryland environments of the Great Plains will have economic advantage for farmers and ranchers growing pearl millet for forage. A field experiment was conducted in 2016 at the Agricultural Research Center-Hays, KS, to investigate N and P fertilizer application effects on forage yield and nutritive value of pearl millet. Factorial combinations of five levels of N (0, 30, 60, 90, and 120 lb/a) and three levels of P (0, 15, and 30 lb/a) were evaluated in randomized complete block design with four replications. A forage-hybrid cultivar, TifLeaf 3, released by U.S. Department of Agriculture, Agricultural Research Service (USDA-ARS) unit at the University of Georgia (Tifton, GA) was used for the experiment. The seed was drilled in six rows at 15 lb/a in individual plot sizes of 5 ft wide × 30 ft long. The results indicate that N fertilizer application increased forage yield, crude protein content, andin vitrodry matter digestibility. Although increase in N rate increased the protein content and digestibility of the forage, this single season on-station experiment indicates that N rate of 30 lb/a is adequate for pearl millet forage production under rain-fed conditions. Application of P fertilizer had no effect on forage yield. However, applying 15 lb P/a did increasein vitrodry matter digestibility compared to the check treatment.
Keywords: Pearl millet; nitrogen; phosphorus; forage yield; nutritive value; TifLeaf 3